2021
DOI: 10.53771/ijbpsa.2021.2.2.0090
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the clinical-pathological factors and prognosis in breast cancer young surviving women who had a subsequent pregnant

Abstract: Objective. To elucidate the impact of clinical-pathological factors on overall survival (OS) in patients who got pregnant after breast cancer treatment. Methods. Retrospective cohort of women age younger than 40 years with breast cancer history without active disease at diagnosis of postcancer pregnancy. Clinical-pathological factors were analized by age group and recent birth. Overall survival (OS) was evaluated from Kaplan-Meier method. The association between clinical-pathological factors and OS was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The NPI also predictes risk groups in PABC women or in the postpartum 21, 38 . However, Lambertini at el.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The NPI also predictes risk groups in PABC women or in the postpartum 21, 38 . However, Lambertini at el.…”
Section: Discussionmentioning
confidence: 97%
“…Young age at diagnosis is considered a poor prognostic factor, since has an increased risk of distant recurrence and death compared to middle and older-aged women 15, 29, 35-38 . Several studies have found a high mortality rate in younger women, particularly in ER-positive and luminal tumors 16, 25, 29, 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations